88. Onabotulinumtoxin-A improves chronic migraine: An open label, single-center, post-marketing prospective study. Issue 1 (January 2015) - Bianchi, F.; Colombo, B.; Amadio, S.; Guerriero, R.; Butera, C.; Cursi, M.; Elia, P.; Comi, G.; Del Carro, U.
<x xml:space="preserve">Abstract</x> Data from large multicenter clinical trials (PREEMPT) demonstrated efficacy and safety of onabotulinumtoxin A for prophylactic treatment of chronic migraine (CM), prophylactic drug-free patients. This study aimed to confirm the efficacy of onabotulinumtoxin A in CM patients with unsatisfactory chronic polytherapy. 26 CM patients (18 females) taking multiple prophylactic/symptomatic medications entered the study. The overall dose ranged between 155 and 170 U administered in 31–34 sites following PREEMPT protocol, repeated at 12 weeks intervals. Main efficacy variables included number of headache/migraine days and episodes, total cumulative headache hours, MIDAS and HIT-6 scores; all items were assessed at baseline and at the 12th-week and 24th-week follow-up. The following variables showed statistically significant changes at 12th-week time-point: headache/migraine days, moderate/severe headache days, migraine episodes, total cumulative hours of headache; slight, not significant MIDAS and HIT-6 scores' improvement was observed. All the efficacy indicators further improved at the 24-week follow-up, even though only headache days and >4 h episodes number were significant. Adverse event were uncommon and did not require treatment discontinuation. Treatment with onabotulinumtoxin A reduced frequency and duration of headache, as well as need for drug consumption and was well tolerated in most cases.